2015
DOI: 10.1074/jbc.m114.624056
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Pharmacological Inactivation of the MYCN Gene Network as a Therapeutic Strategy for Neuroblastic Tumor Cells

Abstract: Background: Neuroblastic tumors are often addicted to the MYCN protooncogene.Results: Using a genome wide shRNA screen, we have identified key MYCN synthetic lethal genes.Conclusion: Chemical inhibition of the newly identified MYCN synthetic lethal genes selectively kills MYCN-amplified cell lines.Significance: Decoding the MYCN gene network will help to develop drugs for the treatment of neuroblastic tumors with activated MYCN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 65 publications
3
38
0
Order By: Relevance
“…a, b, d, and e). Both activating and inactivating phosphorylations of CDC2, respectively, at Thr161 and Tyr15 [Nebreda, ; Chayka et al, ], were decreased in both investigated neuroblastoma cell lines overexpressing the wild‐type form of MCPIP1, as well as the mutant form MCPIP1‐ΔPIN, after normalization to reference protein—GAPDH (Fig. a, b, d, and e).…”
Section: Resultsmentioning
confidence: 99%
“…a, b, d, and e). Both activating and inactivating phosphorylations of CDC2, respectively, at Thr161 and Tyr15 [Nebreda, ; Chayka et al, ], were decreased in both investigated neuroblastoma cell lines overexpressing the wild‐type form of MCPIP1, as well as the mutant form MCPIP1‐ΔPIN, after normalization to reference protein—GAPDH (Fig. a, b, d, and e).…”
Section: Resultsmentioning
confidence: 99%
“…Around 50% of HR-NB have an amplification of the MYCN oncogene, which drives proliferation and causes replication stress (117). MYCN also transcriptionally upregulates many proteins involved in DNA DSB repair, including components of the MRE11-RAD50-NBLS1 (MRN) complex (118,119), alternative NHEJ (alt-NHEJ) (120), and Bloom syndrome (BLM) helicase (121), and the cell cycle checkpoint protein CHK1 (117,122). Upregulation of these genes likely provide MYCNdriven tumors the ability to tolerate higher levels of DNA damage and replication stress.…”
Section: Ddr Defects In Neuroblastomamentioning
confidence: 99%
“…Inhibition of CKS1B is synthetically lethal with MYCN amplification/overexpression in neuroblastoma cells, suggesting that it may be used to target specifically MYC high tumours 12 . As RNA interference is not yet a viable option in cancer therapy, we used Prozac to disrupt the CKS1-SKP2 interaction, with the aim of causing stabilisation of the product of the tumour suppressor gene CDKN1B -P27 Kip1 -, in neuroblastoma cell lines.…”
Section: Expression In Neuroblastoma Cell Linesmentioning
confidence: 99%
“…Further studies have additionally shown that in neuroblastoma cells MYCN targets a separate Ebox location and, similarly to c-MYC, augments transcription of SKP2 11 . Furthermore, c-MYC and MYCN induce CKS1B transcription 10,12 . Targeting SKP2 causes p53-independent apoptosis in non-amplified neuroblastoma cells, whereas in MYCN-amplified cells it was noted a decrease in growth but not apoptosis 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation